Pengaruh Personal Preference, Sumber Daya dan Budaya Terhadap Kepatuhan Diet Penderita Diabetes Mellitus - Wahyu Rahmawati; Henry Sudiyanto; Yusuf Alamudi; Ni Made Parwati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Diabetes Mellitus (DM) is a chronic disease that requires strong adherence in its management. However, dietary compliance is often influenced by demographic, psychosocial, resource, and cultural factors. The purpose of this study was to analyze the influence of demographic factors, cognition and emotion, personal preferences, resources, and culture on dietary adherence among DM patients at Bhayangkara H.S. Samsoeri Mertojoso Hospital, Surabaya. This study employed a cross-sectional design with a sample of 105 DM patients. Data were collected using a structured questionnaire and analyzed through logistic regression. The findings revealed that the majority of respondents were non-adherent to the DM diet. Demographic factors (age, sex, education, occupation, marital status) contributed 41.3% to dietary adherence. Knowledge, attitudes, and personal preferences explained 63.7% of the variation, while limited resources and negative cultural practices increased the risk of non-adherence by 27.8–41.7 times. Respondents who adhered to the dietary recommendations tended to have better-controlled blood glucose levels. Logistic regression analysis indicated that demographic factors collectively influenced dietary adherence (p = 0.000). In addition, cognition and emotion (knowledge and attitudes) along with personal preferences significantly affected DM dietary compliance (p = 0.000). Furthermore, resource constraints and cultural influences related to lifestyle and health history were also significantly associated with dietary adherence (p = 0.000). In conclusion, dietary adherence in DM is not solely a matter of individual discipline but rather the result of a complex interaction between knowledge, attitudes, social support, access to resources, and cultural values. Culturally sensitive educational approaches, strengthening family support, and human-centered interventions are essential strategies to ensure successful DM management